Escola montessoriana: um ambiente preparado - SOUZA, Danarah Santos Lima; SOUZA, Fabrício Ramos de; ASSIS, Kemelly César Alcântara de; PEREIRA, Mayara Dias (285, 2023)
O presente estudo propõe o design de espaços projetados de uma Escola Montessoriana para crianças de 3 a 6 anos, reconhecendo a importância crucial do ambiente escolar no desenvolvimento infantil. Fundamentado nos princípios do Método Montessori, este projeto busca criar um espaço cuidadosamente projetado para estimular a autonomia, criatividade e amor pelo conhecimento nas crianças. O objetivo central é criar ambientes educacionais estimulantes e pertencentes aos alunos, onde móveis e elementos são dispostos à altura acessível, tonalidades pastéis e ambientes claros que promovem tranquilidade e a presença de plantas que contribui para o bem-estar. A metodologia adotada abrange a investigação dos fundamentos teóricos de Maria Montessori e do Design de Interiores voltado para espaços educacionais. Além disso, a análise de estudos de caso serve como referência para a aplicação bem-sucedida desses princípios. Em síntese, este trabalho visa não apenas a composição visual, como também a promoção do pleno desenvolvimento infantil por meio de ambientes minuciosamente planejados, estimulando os pequenos a se tornarem aprendizes independentes e curiosos.

This study proposes the design of spaces for a Montessori School catering to children aged 3 to 6, recognizing the crucial importance of the school environment in child development. Grounded in the principles of the Montessori Method, this project seeks to create a meticulously designed space to stimulate autonomy, creativity, and a love for knowledge in children. The central goal is to establish stimulating educational environments that belong to the students, where furniture and elements are arranged at accessible heights, pastel tones and bright spaces promote tranquility, and the presence of plants contributes to well-being. The adopted methodology encompasses the investigation of the theoretical foundations of Maria Montessori and Interior Design tailored for educational spaces. Additionally, case studies' analysis serves as a reference for the successful application of these principles. In summary, this work aims not only for visual composition but also to promote comprehensive child development through meticulously planned environments, encouraging the little ones to become independent and curious learners.
This study proposes the design of spaces for a Montessori School catering to children aged 3 to 6, recognizing the crucial importance of the school environment in child development. Grounded in the principles of the Montessori Method, this project seeks to create a meticulously designed space to stimulate autonomy, creativity, and a love for knowledge in children. The central goal is to establish stimulating educational environments that belong to the students, where furniture and elements are arranged at accessible heights, pastel tones and bright spaces promote tranquility, and the presence of plants contributes to well-being. The adopted methodology encompasses the investigation of the theoretical foundations of Maria Montessori and Interior Design tailored for educational spaces. Additionally, case studies' analysis serves as a reference for the successful application of these principles. In summary, this work aims not only for visual composition but also to promote comprehensive child development through meticulously planned environments, encouraging the little ones to become independent and curious learners.
Keywords: Arquitetura de interiores; Ambiente escolar; Instituições de ensino; Métodos de ensino; Mobiliário infantil; Produção Cultural e Design